Rice Root Distribution of Four Rice Varieties to Different Depth of Submergence - Arinal H.I. Nurrahma; Ahmad Junaedi; Heni Purnamawati; Jun-Ichi Sakagami (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
Rice (Oryza sativa L.) is largely cultivated in lowland area that vulnerable to flood occurrence. Root supposed to play an important role on rice tolerance to submergence stress. An experiment which conducted from January to May 2014 in Cikarawang Field Laboratory, Darmaga, Bogor, West Java aimed to study the role of root distribution on rice submergence tolerant. The experiment used Split Plot design replicated three times, with the depth of submergence as main plot and rice variety as subplot. The main plot consisted of water depth of 5 cm (optimum), 50 cm, 60 cm and 80 cm from soil surface. The subplot consisted of four rice varieties, namely Ciherang, Inpari 30 (Ciherang Sub1), Indragiri and Margasari. Each plant was planted in a root box (30 cm x 40 cm x 5 cm) which put into container (67 cm x 47 cm x 42 cm) and placed into the pond with water depth as treatment. Submergence started when the plant was 39 DAS (Days After Seeding) for ten days. Observation conducted after the submergence stopped (49 DAS). Result showed that submergence retarded plant growth, root distribution and increase root damage for all rice varieties with the biggest effect on susceptible varieties.